La protection des consommateurs et l’assurance - Moreau, Rémi (Assurances, 1996)
The rise of consumerism as a powerful force is one of the major social developments in insurance in the last two decades, particularly since the 1974 insurance law reform and the 1994 new civil code. The author describes several legislative provisions and recent decisions regarding consumer protection and their possible impact on insurance principles. The thrust of the consumerist movement focuses on the discrepancy between insurance policies and their application, the distinction between insurance coverage and scope of coverage, the insured's reasonable expectation and many others court interpretations in favor of the insured.